Raman image-activated cell sorting - Nao Nitta; Takanori Iino; Akihiro Isozaki; Mai Yamagishi; Yasutaka Kitahama; Shinya Sakuma; Yuta Suzuki; Hiroshi Tezuka; Minoru Oikawa; Fumihito Arai; Takuya Asai; Dinghuan Deng; et al. (Nature Communications, 2020)
Most current cell sorting methods are based on fluorescence detection with no imaging capability. Here the authors generate and use Raman image-activated cell sorting with a throughput of around 100 events per second, providing molecular images with no need for labeling.